2017
DOI: 10.1186/s12967-017-1159-y
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant T cell responses in the bone marrow microenvironment of patients with poor graft function after allogeneic hematopoietic stem cell transplantation

Abstract: BackgroundPoor graft function (PGF) is a life-threatening complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Nevertheless, whether abnormalities of T cell subsets in the bone marrow (BM) immune microenvironment, including Th17, Tc17, Th1, Tc1, Th2, Tc2 cells and regulatory T cells (Tregs), are involved in the pathogenesis of PGF remains unclear.MethodsThis prospective nested case–control study enrolled 20 patients with PGF, 40 matched patients with good graft function (GGF) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Collectively, the evidence shows that changes in MФ differentiation, polarization, and activation in the local milieu can play a decisive role in the pathogenesis of autoimmune and inflammatory diseases. Recently, we reported that elevated BM Th1/Th2 and Tc1/Tc2 ratios were involved in the occurrence of PGF (Wang et al , ; Kong et al , ). Consistent with the previous reports and our previous work, we found an aberrant monocyte distribution and MФ polarization towards M1 in the BM of PGF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, the evidence shows that changes in MФ differentiation, polarization, and activation in the local milieu can play a decisive role in the pathogenesis of autoimmune and inflammatory diseases. Recently, we reported that elevated BM Th1/Th2 and Tc1/Tc2 ratios were involved in the occurrence of PGF (Wang et al , ; Kong et al , ). Consistent with the previous reports and our previous work, we found an aberrant monocyte distribution and MФ polarization towards M1 in the BM of PGF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports indicate that dysregulated Th1 cell/Th2 cell, Tc1 cell/Tc2 cell, and Th17 cell/Treg ratios in the BM immune microenvironment are involved in the pathogenesis of PGF (Wang et al , ; Kong et al , ). In the current study, MФs reached unbalanced polarization states that were similar to the Th1/Th2 polarization state, which represents an activated immune state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine studies demonstrated that effective hematopoiesis in the bone marrow (BM) depends on the interaction between HSCs and the specific BM microenvironment [5][6][7][8]. Therefore, in previous studies we focused on the quantity and function of HSCs and BM microenvironment elements in PGF patients [9][10][11][12][13][14]. Lower numbers and dysfunctional characteristics of CD34 + cells were found in the BM of PGF patients [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, defective BM endosteal cells, endothelial progenitor cells, and perivascular cells were present in PGF patients [9,12,13]. In addition, aberrant T cell responses were observed in the BM microenvironment of PGF patients [10,14]. Despite considerable progress, the mechanisms involved in the pathophysiology of PGF remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%